Clinical Characteristics and Early Findings of Coronavirus Disease (Covid-19) at a Tertiary Care Teaching Hospital in Pakistan - Waseem Iqbal, Uroosa Iram, Moiz Inam Khan, Nazish Farooq, Amna Iram, Zahid Rehman, Mati Ullah, Ihsan Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Severe acute respiratory syndrome-2 (SARS-CoV-2) emerged as a novel coronavirus and associated with the pandemic. In our study we observed the clinical characteristics, early findings, and its association with comorbidity. Methods: A single center retrospective study was carried out in Mardan Medical Complex (MMC), Khyber Pakhtunkhwa (KP), Pakistan from May 21st, 2020 to June 30th, 2020. Altogether three thousand, one hundred and fifteen (n=3115) COVID-19 suspected patients were included in the current study. Briefly nasopharyngeal swab, sputum and blood were collected. The viral amplification was carried out by qualitative RT-PCR using commercially available kit and routine laboratory tests of all the suspected patients were performed. Results: Using RT-PCR total 19.8% (n=613/3115) confirmed cases of COVID-19 were observed. The majority were males’ patients. The most common comorbidity was type-2 diabetes (T2DM); 24.8% followed by cardiovascular diseases; 6% and T2DM with cardiovascular disease 3.1%. Among the infected patient’s leukocytosis was observed in 43% patients and 27.9% had abnormal findings on X-rays. The RNA detection efficacy from the sputum, nasopharyngeal swab, and blood specimens were 30%, 25.3% and 9.6% respectively. In total, 18.3% patients were critical, and 14.5% patients were on ventilator and the reported mortality rate were 5.2%. Conclusion: Overall, the COVID-19 patients observed in our study was comorbid and asymptomatic or with mild symptoms like fever, cough, and shortness of breath. Higher, RNA detection efficacy was observed from sputum. Keywords: COVID-19, RT-PCR, T2DM, Clinical characteristics, comorbidity, Pakistan